Air-Stable NaxTMO2 Cathodes for Sodium Storage - Zhang, Yi; Zhang, Renyuan; Huang, Yunhui (Frontiers in Chemistry, 2019)
Sodium-ion batteries are considered to be the most promising alternative to lithium-ion batteries for large-scale stationary energy storage applications due to the abundant sodium resource in the Earth’ crust and as a result, relatively low cost. Sodium layered transition metal oxides (NaxTMO2) are proper Na-ion cathode materials because of low cost and high theoretical capacity. Currently most researchers focus on the improvement of electrochemical performance such as high rate capability and long cycling stability. However, for NaxTMO2, the structure stability against humid atmosphere is essentially important since most of them are instable in air, which is not favorable for practical application. Here we provide a comprehensive review of recent progresses on air-stable NaxTMO2 oxides. Several effective strategies are discussed, and further investigations on the air-stable cathodes are prospected.